Dominant dystrophic epidermolysis bullosa presenting with milia. - Kaya, T.I.; Tursen, U.; Baz, K.; Kokturk, A.; Ikizoglu, G. (European Journal of Pediatric Dermatology, 2002)
Dominant dystrophic epidermolysis bullosa (EB) is a rare disorder, which usually presents with bullous lesions, especially located on the bony prominences of the extremities. Characteristically, these bullous lesions heal with milia formation and scarring. We describe a 4-month-old boy with dominant dystrophic EB, who presented only with milia. Grouped milia lesions appeared on the dorsal aspects of his hands months before the typical bullous lesions appeared. The aim of this report is to emphasize that milia can be the first sign of epidermolysis bullosa and they can be a clue to early diagnosis of this disease.